Quantifying head impacts and neurocognitive performance in collegiate boxers - Doan, B. K.; Heaton, K. J.; Self, B. P.; Butler Samuels, M. A.; Adam, G. E. (Journal of Sports Sciences, 2022)
Head impacts and neurocognition were quantified in 27 intercollegiate male boxers engaged in two, two-minute sparring rounds. Head impacts were measured using Instrumented Boxing Headgear (IBH). Pre and post-sparring neurocognitive performance was compared using two computerized neuropsychological test batteries (CNTs): Immediate Post-concussion Assessment and Cognitive Testing (ImPACT™) and Automated Neuropsychological Assessment Metrics - Military Battery (ANAM4® MIL). An average of 27.63 ± 17.87 impacts above the 9.6 g IBH threshold were recorded per boxer, with average peak linear acceleration of 23.48 ± 15.20 g and average peak rotational acceleration of 1761.40 ± 1064.34 rad/s2. Small, but measurable declines in delayed memory and improvement in response time from pre- to post-bout were noted. Number of impacts and concussion history predicted degraded memory performance. This is a unique quantification of head impacts in collegiate boxing, which were similar in frequency and location, but lower in magnitude as compared to amateur boxing. Improved understanding of impact kinematics may enhance safety in boxing and other contact sports. Subtle post-bout decrements in delayed memory performance and mild improvement in response time reinforce prior research and provide evidence of congruence in our two CNT assessments, which may facilitate comparisons of outcomes across settings utilizing these tests.